Quality of life in the regions: An exploratory spatial data analysis for West German labor markets - Karsten Rusche (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2008)
Which of Germanys regions is the most attractive? Where is it best to live and work - on objective grounds? These questions are summed up in the concept quality of life. This paper uses recent research projects that determine this parameter to examine the spatial distribution of quality of life in Germany. For this purpose, an Exploratory Spatial Data Analysis is conducted which focuses on identifying statistically significant (dis-)similarities in space. An initial result of this research is that it is important to choose the aggregation level of administrative units carefully when considering a spatial analysis. The level plays a crucial role in the strength and impact of spatial effects. In concentrating on various labor market areas, this paper identifies a significant spatial autocorrelation in the quality of life, which seems to be characterized by a North-Mid-South divide. In addition, the ESDA results are used to augment the regression specifications, which helps to avoid the occurrence of spatial dependencies in the residuals.
Keywords: D63; R10; R12; R50; 330; Quality of Life; Exploratory Spatial Data Analysis; Functional Economic Areas; Spatial Econometrics; LISA Dummies